El medio ambiente y su influencia en el desarrollo socio afectivo de los niños y las niñas del primer año de educación general básica de la escuela fiscal “Luis Godin” de la parroquia de Yaruqui, del cantón Quito de la provincia de Pichincha. Periodo 2013 – 2014 - Jumbo Proaño, Diana Carolina (2015)
This research work, entitled: "Environment and its influence on the socio affective of the children of the first year of General Basic Education of the Public School "Luis Godin” Yaruqui Parish, Quito Canton Pichincha Province. Period 2013 - 2014 "has been structured and developed in accordance with Regulation of Academic System of the National University of Loja. The central problem is how the environment influences Affective Development Partner of the children of the first year of basic general education school tax "Luis Godin" The overall objective was formulated: Inquire about the influence of the environment on socio affective development of children in the first year of basic general education school "Luis Godin" Parish Yaruqui, the canton of Quito Pichincha Province. The methods used were the Scientific, Inductive, Deductive, Analytical method - Synthetic, Descriptive and Statistical Model, the techniques applied are the survey and observation sheet for collecting information and complement the development of the theoretical framework. The results of the survey of teachers with the question Do you think that the environment around the child influences their emotional development partner? 100% said that evidently the environment in which the learner operates daily direct impact on the socio-emotional development thereof; 100% consider agree that parents are encouraged to family affection to improve the child's environment In the survey of Parent; 59.78% say that both mom and dad are working consequently the 38.04% agree that most of the time are older siblings who are caring younger children are overprotected, while 56 % mentioned that they are not. In both the observation guide given to children benchmarks to evaluate the performance of the learner regarding the surrounding environment, was evident in 75% aspects stipulated are achieved using generating uncertainty and delay in the process was considered teaching.